Scattering amplitudes, Wilson loops and the string/gauge theory correspondence - Alday, L; Roiban, R (2008)
We review, in a self-contained and pedagogical manner, recent developments and techniques for the evaluation of scattering amplitudes of planar N = 4 SYM theory at both weak and strong coupling. Special emphasis is placed on the newly discovered connection between a special class of amplitudes and the expectation values of particular cusped light-like Wilson loops. © 2008 Elsevier B.V.